Emerging Lipid-based Carriers for Systematic Utilization in the Pharmaceutical and Biomedical Sciences: A Review - Kendre, Prakash N.; Kayande, Dhiraj R.; Pote, Ajinkya K.; Kanthale, Sanagmeshwar B.; Prajapati, Bhupendra G.; Kendre, Yuvraj; Jain, Shirish (Pharmaceutical Nanotechnology, 2025)
Emerging lipid-based carriers are revolutionizing drug delivery in the pharmaceutical and biomedical sciences. These innovative carriers harness the unique properties of lipids to improve the solubility, stability, and targeted delivery of therapeutic agents, ushering in a new era of precision medicine. Lipid-based carriers, such as liposomes, lipid nanoparticles, and solid lipid nanoparticles, offer several advantages. They can encapsulate both hydrophilic and hydrophobic drugs, enabling the delivery of a wide range of compounds. Additionally, lipids are biocompatible and biodegradable, minimizing the risk of toxicity. Their ability to mimic cell membranes allows for enhanced cellular uptake and controlled release, optimizing drug efficacy while minimizing side effects. Furthermore, lipid-based carriers are ideal for delivering drugs to specific sites within the body. By modifying the lipid composition, surface charge, and size, researchers can tailor these carriers to target tumours, inflamed tissues, or specific cells, improving therapeutic outcomes and reducing systemic toxicity. In summary, emerging lipid-based carriers are poised to transform pharmaceutical and biomedical sciences by addressing critical challenges in drug delivery. These carriers enhance drug stability, bioavailability, and targeted delivery, offering the potential to revolutionize the treatment of various diseases and improve patient outcomes. As research in this field continues to advance, we can expect even more sophisticated lipid-based carrier systems to emerge, further expanding the possibilities for precision medicine. This review focuses on the contribution of lipid carriers in the pharmaceutical and biomedical sciences.
Keywords: lipid-based carriers